1985
DOI: 10.1002/ijc.2910360505
|View full text |Cite
|
Sign up to set email alerts
|

Prospective studies on nasopharyngeal carcinoma in epstein‐barr virus IgA/VCA antibody‐positne persons in Wuzhou city, china

Abstract: A serological mass survey was carried out in Wuzhou City in 1980, 1,136 IgA/VCA-positive persons being followed up for 4 years. Altogether 35 NPC cases were detected, of which 15 (43%) were in stage I and 17 (48.5%) in stage II, early cases (I + II) thus amounting to 91.5%. The detection rate of early cases was 2.9 times higher than in our outpatient clinic. IgA/VCA antibody could be detected 16-41 months prior to clinical diagnosis of NPC. We conclude that, if IgA/VCA-positive individuals are examined routine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
122
0
3

Year Published

1991
1991
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(129 citation statements)
references
References 3 publications
4
122
0
3
Order By: Relevance
“…Another 6.5% has a moderate level of risk with odds ratios of 4 to 10. This is similar to the risk level sustained by those who have elevated levels of VCA IgA antibody determined by the traditional test, 5,7,[15][16][17] and the knowledge of the risk serves to alert these individuals and their physicians to early symptoms of NPC. In addition, the combined test results serve to identify a third group comprising an estimated 0.4% of HS, who are at high risk of NPC with an odds ratio of 138.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Another 6.5% has a moderate level of risk with odds ratios of 4 to 10. This is similar to the risk level sustained by those who have elevated levels of VCA IgA antibody determined by the traditional test, 5,7,[15][16][17] and the knowledge of the risk serves to alert these individuals and their physicians to early symptoms of NPC. In addition, the combined test results serve to identify a third group comprising an estimated 0.4% of HS, who are at high risk of NPC with an odds ratio of 138.…”
Section: Discussionmentioning
confidence: 67%
“…Previous population studies carried out in high-incidence areas for NPC estimated the occurrence of the cancer among apparently healthy subjects having an elevated serum level of VCA IgA to be about 1% per year. 4,5,7 In practice, this serves to alert the individuals and clinicians to early symptoms of the cancer.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although several previous studies [2][3][4][5] have reported on the use of EBV serology for screening and early detection of NPC, the role of EBV DNA detection as a screening test for NPC remains to be defined. Circulating cell-free EBV DNA is detectable in the plasma of 96% of NPC patients 6 by quantitative real-time polymerase chain reaction (PCR) and has been shown to be a useful marker in prognostication 7 as well as residual disease detection.…”
Section: Dear Sirmentioning
confidence: 99%
“…Although several prior studies (Zeng et al, 1982;Zeng et al, 1983;Zeng et al, 1985;Tsang et al, 2004) have demonstrated on the use of EBV serology for screening and early detection of NPC, the role of EBV DNA detection as a screening test for NPC remains inconclusive. Previous research has reported that cell-free EBV DNA can be quantitatively measured in the blood of NPC patients using polymerase chain reaction (PCR) technique Shotelersuk et al, 2000;Lin et al, 2001;Chan et al, 2003;Fan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%